Young black MSM's exposures to and discussions about PrEP while navigating geosocial networking apps. Issue 1 (2nd January 2021) - Fields, Errol L.; Thornton, Nicole; Long, Amanda; Morgan, Anthony; Uzzi, Mudia; Arrington-Sanders, Renata; Jennings, Jacky M.
Abstract: Young Black gay, bisexual and other men who have sex with men (YBMSM) carry a disproportionate HIV burden perpetuated by exposure to sexual networks with higher untreated HIV prevalence and incidence. In Baltimore, these sexual networks include high utilization of geosocial networking apps (GSN-apps). Our prior work suggests these apps can be important access points for targeted interventions like PrEP. To inform online PrEP outreach we explored YBMSM GSN-app users' exposure to and discussions about PrEP while navigating apps. We actively recruited YBMSM ( n  = 17) age 18–24 from the GSN-app most frequently reported by MSM newly diagnosed with HIV in Baltimore. Participants were recruited through direct messaging within the GSN-app while logged-on in high HIV transmission areas. Participants completed 60–90 minute semi-structured interviews, which were analyzed using a 3-stage analytic coding strategy. While some participants had not heard of PrEP, the majority described mentions or conversations about PrEP on GSN-apps. Three themes emerged: (1) Mistrust of PrEP, (2) Association with sexual promiscuity, and (3) Concerns about lack of protection from other STIs. Proper messaging, accurate information, and education are needed to account for the negative perceptions that surround PrEP; otherwise, continued underuse among YBMSM will expand rather than reduce HIV disparities.